2021
DOI: 10.31234/osf.io/nuksd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probability disclosures are not enough: Reducing loot box reward complexity as a part of ethical video game design

Abstract: Loot boxes in video games provide randomised rewards that bear structural similarities to gambling. Current loot box consumer protection measures, such as requiring probability disclosures, have been inspired by similar approaches in gambling. However, current loot box rewards are too complex for consumers to be meaningfully protected by probability disclosures alone. But as digital goods, loot boxes can be redesigned in more ethical ways. Four reductions to loot box reward complexity are proposed: capping the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Therefore, rather than banning the sale of loot boxes entirely or not regulating it at all despite the legitimate consumer protection concerns, a third alternative middleground strategy is the adoption of 'ethical game design' that seeks to reduce or remove seemingly particularly problematic aspects of loot boxes (King and Delfabbro 2019;Xiao and Henderson 2021;Xiao and Newall 2021). Both companies and players can still benefit from the loot box monetisation model (their economic interests and freedoms are not infringed upon), but players are provided with loot boxes that are less likely to harm and thereby better consumer protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rather than banning the sale of loot boxes entirely or not regulating it at all despite the legitimate consumer protection concerns, a third alternative middleground strategy is the adoption of 'ethical game design' that seeks to reduce or remove seemingly particularly problematic aspects of loot boxes (King and Delfabbro 2019;Xiao and Henderson 2021;Xiao and Newall 2021). Both companies and players can still benefit from the loot box monetisation model (their economic interests and freedoms are not infringed upon), but players are provided with loot boxes that are less likely to harm and thereby better consumer protection.…”
Section: Discussionmentioning
confidence: 99%
“…However, that reduction would be less than if all players' spending was limited. In addition, some previously non-spending and low-spending players might be more encouraged to now spend more money if they deem the game as being 'fairer' and more ethical (e.g., if spending large sums of money is not necessary to gain a competitive advantage and loot boxes only provide cosmetic benefits, i.e., 'pay-to-win' is not adopted (Zendle et al 2019c)) (Xiao and Newall 2021).…”
Section: Defining Loot Box 'Harm': Only a Small Percentage Of Players...mentioning
confidence: 99%
“…446). Less restrictive, less ‘draconian’ regulatory approaches to minimising potential loot box harms are available ( King & Delfabbro, 2019b ; Xiao & Henderson, 2021 ; Xiao & Newall, in press ), e.g. , mandating probability disclosures, as adopted in the PRC, ironically ( Xiao, Henderson, Yang, & Newall, 2021 ).…”
Section: Alleged ‘Draconian-ness’mentioning
confidence: 99%
“…A survey of Chinese video game players found that 85% of loot box purchasers reported seeing probability disclosures (meaning that they have been reasonably widely seen by players); however, only 19% of this group reported spending less money on loot boxes as a result of seeing the disclosures [24]. This suggests that loot box probability disclosures may be of limited effectiveness at reducing loot box spending even if they are accessibly and prominently displayed such that all players can see them [42]. The video game industry has been widely supportive of loot box probability disclosure as an industry selfregulatory measure aimed at ensuring consumer protection [41], but whether self-regulation is effective remains to be assessed by future research.…”
Section: Potential Harms: Links With Problem Gamblingmentioning
confidence: 99%
“…However, despite the potential for indirect loss, video game companies are still financially able to give out their most valuable rewards more frequently than traditional gambling operators. This means that loot box consumer protection methods do not have to be limited to what has been done in gambling contexts, and that loot box consumers could be additionally protected by novel features of ethical game design, e.g., allowing players to win valuable rewards more often [37,38,42].…”
Section: Potential Harms: Links With Problem Gamblingmentioning
confidence: 99%